Investigation of the observation conditions on the terrain of war operation using GIS technology - Hashimov, Elshan Giyas oğlu; Bayramov, Azad Agalar oğlu (НТУ "ХПІ", 2017)
The modern geoinformation systems (GIS) have been widely applied in Armed Forces for preparation and control of battle operations, for information providing of tactic activities, for improvement of topographic maps etc. In real situations during war activity the Geography information about situation on the terrain can be ofthen changed. So, in this cause the application of usual maps isn’t effective. Only the modern automated control systems can provide fast changing information documenting. The observation condition is one of the terrain features for providing information about enemy troops position and facilities. This feature helps to detemine the distance of sight between any observation points, the invisibility factors of terrain. It is depended on nature of relief plant cover, human settlements and other objects, also meteorological conditions, influencing on the visibility. As result of correct organization of observation, the obtained data help commander to estimate completely the military operation area and adopt a reasonable deсision. In paper the observation conditions between two points of mountain terrain during battle operation have been investigated using GIS technology. The experiments for estimation of observation situation in mountain terrain has been carried out for one of the chosen region of the Caucasus. The visible and invisible areas have been revealed on the line of sight between two selected oversight points. The invisibility factors have been calculated and studied in depended on camera platform height. The visible and invisivle areas are determined under 0-180° angle in range 17941.16 m. The height profile between observations points and the digital heights model of investigated terrain have been constructed and analysed. At the various heights of camera observation platform the 3D heights models of the visible and invisivle areas have been constructed The invisibility factors between two delected viewpoints have been calculated. It is determined that if the heght of camera platform is increased above-ground level then the invisible area is decreased. ArcGIS software has been used for development and calculation measured results.

Сучасні геоінформаційні системи (ГІС) широко використовуються в Збройних Силах для підготовки і управління бойових операцій, для інформаційного забезпечення тактичних дій, для поліпшення топографічних карт. В реальній ситуації під час військових дій геоінформація про становище на місцевості може часто змінюватися. Тому, в цьому випадку застосування звичайних карт не ефективно. Тільки сучасні автоматизовані системи управління можуть забезпечити швидко мінливу інформаційну документацію. Умова спостереження є одним з властивостей місцевості, що забезпечує інформацією про позицію ворожих військ і військової техніки. Це властивість допомагає визначити відстань спостереження між точками спостереження, фактор невидимості місцевості. Це залежить від природи рельєфу рослинного покриву, поселень і інших об'єктів, а також метеорологічних умов, що впливають на видимість. Як результат правильної організації спостереження, отримані дані допомагають командиру повністю оцінити область військової операції і прийняти прийнятне рішення. У статті, використовуючи ГІС технологію, досліджені умови спостереження між двома точками гірській місцевості під час бойової операції. Експерименти по оцінці ситуації спостереження в гірській місцевості були проведені в одній з обраних регіонів Кавказу. По лінії огляду між двома обраними точками спостереження були виявлені видимі і невидимі області. Були розраховані фактори невидимості і вивчені в залежності від висоти платформи камери. Були визначені видимі і невидимі області в радіусі 17941.16 m під кутами 0-180 °. Був побудований і проаналізовано профіль висот між точками спостереження і цифрова модель висот досліджуваної території. Для різних висот розташування платформи з камерою були побудовані і досліджені 3D моделі висот для видимих і невидимих областей. Були розраховані фактори невидимості між двома обраними точками спостереження. Було встановлено, що чим вище платформа з камерою спостереження, тим менше невидима площа. Для обробки і розрахунку виміряних результатів було використано програмне забезпечення ArcGIS.
Дослідження умов спостереження c використанням ГІС технологій на території військових дій
Keywords: observation conditions; mountain terrain; GIS; invisibility factor; height profile; ArcGIS software; умови спостереження; гірська місцевість; ГІС; фактор невидимості; профіль висот; програмне забезпечення ArcGIS